P535 Association of anti-Infliximab antibodies and HLADQA1*05 variant in ulcerative colitis: a retrospective single centre study. (21st January 2022) - Aleman Gonzalez, H; Sankaranarayanan, R; Pattinson, A; Turnbull, J; Katie, S; Whitehead, E; Talbot, A; Myers, S; Sebastian, S
Abstract: Background: The genetic variation HLADQA1*05 has been reported to be associated with anti-Infliximab antibody in CD. The relevance in UC patients receiving infliximab is uncertain. We aimed to evaluate the association of HLADQA1*05 and infliximab antibody formation, treatment changes and infliximab persistence in a real world setting of single centre cohort Methods: Infliximab treated UC patients (n=94) were retrospectively screened for HLDqA1*05. The risk of anti-infliximab antibody formation, absent drug levels in presence of antibody, change in therapy from infliximab were assessed in variant carrying patients in comparison to those without the variants. The proportion of patients needing dose optimisation of infliximab also evaluated Results: Anti-infliximab antibodies were detected in 41.5% of patients in a median follow up of 14.75 (IQR 9–29) months. HLA DQAI*05 was positive in 39.13% of patients. 52.2 % of patients were on concomitant immunomodulators. Higher proportion of patients with HLADQA1*05 developed anti-Infliximab antibodies (59% Vs 24%, p=0.002). Eighty percent of patients who had anti Infliximab antibodies with absent drug levels were positive for HLADQA1*05 with Hazzard Ratio (HR) for development of anti-Infliximab antibodies of 4.54 (95% CI 1.73–11.89) and for antibodies with absent infliximab drug levels 9.86 (95% CI 2.43 -40.01). Higher proportion of HLADQA1*05 patients required dose escalation (78% vs 31%, p=0.001). After adjusting for age, initial infliximab dose and concomitant immunomodulator use, there was no difference anti TNF persistence in patients with HLADQA1*05 variant (HR 2.36, 95% CI 0.89–6.25, p=0.06) Conclusion: Determination of HLADQA1*05 status may identify patients at higher risk of anti-infliximab antibodies in ulcerative colitis. Early intervention with dose optimisation and concomitant immunomodulation may avoid loss of response and facilitate treatment persistence